PEMODELAN GEOID SECARA GRAVIMETRIK DENGAN MENGGUNAKAN DATA GAYABERAT TERESTRIS (STUDI KASUS: PULAU JAWA BAGIAN TENGAH) - Lestari, Rahayu
The Global Navigation Satellite System (GNSS) method is a positioning method that has been significantly developed in geodetic surveying. However, the height obtained through GNSS observations is given in a geodetic height system that needs to be converted to orthometric height for practical measurements in orthometric height systems. One method to convert geodetic height intoto orthometric height is by using geoid undulation model. A very accurate geodetic height can be accessed using GNSS, but the geoid undulation obtained from the current global geopotential model still has limitations in terms of accuracy. Therefore, there is a strong need to model an accurate geoid model to obtain an accurate geoid undulation model to be used for transforming geodetic height into orthometric height. In this study, geoid modeling was carried out using terrestrial gravity data in the central part of Java Island using the Stokes – Helmert’s 2nd condensation Remove-Compute-Restore (RCR) method, SRTM 3” and SRTM 15”+ as topographic data, EGM2008 data as geopotential data. global data, and GNSS/leveling data as data validation. The resulting geoid model has a resolution of 5' and 1', and each model has a standard deviation of 7.2 cm and 4.4 cm. This gravimetric geoid model has better quality than EGM2008, with a standard deviation of 10.7 cm. This study found that the resolution and distribution of the data affect the quality of the resulting geoid model. Therefore, the geoid model’s quality can be improved by using a higher data resolution and model, a more even and dense distribution of terrestrial gravity data, and GNSS/leveling data.